Adaptasi Likelihood of Confusion dalam Pengaturan Persamaan pada Pokoknya dalam Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Athariq Aqilla; Tatty Aryani Ramli (UNISBA Press, 2022)
Abstract. Trademarks are intellectual property in the form of signs that can distinguish goods and/or services in trading activities. Trademark as property, in order to get legal protection, it must be registered and only get protection after the issuance of the certificate. The Indonesian government in order to provide protection for registered mark owners has established regulations that prevent the occurrence of trademark similarities through Law Number 20 of 2016 concerning Marks and Geographical Indications and adapted the likelihood of confusion in these regulations. The purpose of adapting the likelihood of confusion in the regulation is to provide protection both before a dispute occurs and after a dispute occurs. The problem is that until now there are still many similarities disputes in principle against the brand. The purpose of this study is to analyze how to adapt the likelihood of confusion in trademark law, and to analyze the judges' considerations on the